HAMBATAN PEMANGKU KEBIJAKAN DALAM MENGGUNAKAN DATA RUTIN KESEHATAN IBU DAN ANAK UNTUK PERENCANAAN DAN PENGANGGARAN - Brian Sahar Afifah; Lutfan Lazuardi; Tiara Marthias (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: In Indonesia, policy stakeholders’ use of routine health data is still limited because the data are incomplete, not of good quality, and timeliness is still constrained. In MCH (Maternal and Child Health), the use of routine data contributes to the quality of services, MMR (Maternal Mortality Rate) and IMR (Infant Mortality Rate), including in the Special Region of Yogyakarta (DIY). The current pandemic situation has a negative impact on the availability of routine data and the achievements of the MCH program. Thus, it is essential to understand the factors that influence the use of routine data to improve the MCH program during the pandemic. Objective: This study aimed to explore the use of MCH data in the planning and budgeting process for MCH programs and the fac tors that need to be improved in the utilization of MCH data in DIY Province during the COVID-19 pandemic. Methods: This research is descriptive qualitative research that explores barriers to policy stakeholders’ used data in the planning and budgeting process of the MCH program. Research is located in two regencies, Sleman and Gunung Kidul Regencies, DIY Province. Determination of subjects by purposive sampling method, with criteria for stakeholders involved in the planning and budgeting process for the MCH program at the primary health care and health offices. Data analysis using content analysis techniques. Results: The study results found obstacles to using routine MCH data by policymakers, such as low quality of MCH data, Human Resources (HR) quality, an unintegrated MCH information system, internet network, and political interests. In addition, researchers also found lower quality of MCH data during the pandemic. Conclusion: The government needs to increase the use of data in planning and budgeting by using an integrated and simple electronic-based information system to meet MCH information needs. Furthermore, the government needs to make regulations on the integration of MCH information and special SOPs for MCH, improve the quality of human resources for users of information systems, increase HR motivation in respecting MCH information, and need to review PMK policy No. 7 regarding the preparation of MCH planning and budget regarding the timeline for submitting plans. and program budgets.